Analisis Metode Pelaksanaan dan Kinerja Struktur Gedung Parkir Bertingkat Menggunakan Sistem Precast dan Minipile: Studi Kasus Plaza 6 Pondok Indah - Edison Hatoguan Manurung; Sri Hartanto (LPPM Institut Pendidikan Nusantara Global, 2025)
The construction of a multi-story parking building in densely populated areas such as Plaza 6 Pondok Indah is a response to limited land availability and the increasing demand for parking facilities. This project employs modern construction methods, such as minipile foundations and precast structural systems, to accelerate project timelines and maintain on-site efficiency. This study aims to directly examine the implementation process and structural systems used on-site, as well as evaluate their effectiveness in terms of technical performance and construction time. Data were collected through direct observation at the project site, technical documentation, and informal discussions with project personnel. Emphasis was placed on the stages of foundation work, substructure components such as pile caps and tie beams, and the installation of precast components on each floor. Additionally, the installation of steel structures was an essential aspect of this study. Observations revealed that the use of precast floor slabs significantly reduced construction time by minimizing the need for formwork and scaffolding. The steel frame system provided advantages in installation flexibility and faster on-site mobilization. The selection of minipiles as the foundation type was also appropriate for the limited land space and moderate soil bearing capacity. Overall, the construction methods used in this project offered substantial benefits in terms of time and on-site efficiency. This study may serve as an initial reference for similar projects, particularly in utilizing a combination of steel structures, precast elements, and deep foundations.